Shifting the polarity of some critical residues in malarial peptides' binding to host cells is a key factor in breaking conserved antigens' code of silence (2008)
As microbes use many mechanisms for avoiding immunological pressure, new strategies must be developed to bypass the immunological code of silence of conserved, functionally-important amino acid sequences, such as those involved in high activity binding peptides (HABPs) attaching to their host cells. Hundreds of experiments in large numbers of Aotus monkeys revealed that this immunological code of silence could be broken by shifting the polarity of some critical host cell binding residues in these HABPs by substituting F for R and vice versa, YW, LH, IN, PD, MK or E, CT, VN or S; there are special rules for A, G and S. 1H-nuclear magnetic resonance of these modified, immunogenic, protection-inducing HABPs and molecular modelling revealed that such modifications induced appropriate fitting into specific HLA-DR?1* Pockets, suggesting the presence of new pockets and a haplotype- and allele-specific conscious TCR. A highly immunogenic and protection-inducing anti-malarial vaccine can thus be produced.